A continuing mandamus to enforce rights to adequate housing in the era of super typhoons. Issue 1 (September 2021) - Valdez, Amiel Ian
Abstract : The era of super typhoons is here and is predicted to linger due to anthropogenic climate change. Disasters triggered by these typhoons have caused not only loss of lives, but also displacements of people who are left without houses, properties and livelihoods. Using the Philippine experience, this article examines the legal standard of right to adequate housing under the international human rights law and international climate change law, and the Philippines' commitments to these regimes. It argues that the Philippine government's post-typhoon responses are fragmented, reactive, and ephemeral, and that there are gaps in the current housing laws. It is then argued that these issues are incongruent with the minimum standards of adequate housing. To ensure that the housing rights of climate displaced persons are protected, the role of domestic courts in enforcing the government's adaptation commitments under the Paris Agreement using the writ of continuing mandamus is considered.